Relational Governance Project: Towards a Critical Indigenous Policy Studies ... - Wildcat, Matthew Caldwell (University of Alberta Library, 2021)
SSHRC IDG awarded 2021: The objective of the Relational Governance Project (RGP) is to study how First Nations create shared jurisdiction with each other to deliver governmental services.A second objective of the proposed research is examining policy making within Indigenous led institutions what I am calling Critical Indigenous Policy Studies. I anticipate the RGP will last 1015 years and will be guided by two research questions: i) Where and how do First Nations successfully create forms of shared jurisdiction with each other in the delivery of governmental services? ii) What methods and theories are needed for policy research that focuses on Indigenous led institutions? This proposal outlines two pressing research needs. First, the RGP will create a database on the governance of First Nations education authorities in the prairie provinces. Second, the RGP will lead an interview process on Indigenous citizenship that explores the gap between Indigenous peoples’ relational practices and existing First ...